Evolution of match performance parameters in elite men's handball 2012-2022 - Pascual, A.; Font, R.; Pascual, X.; Lago-Peñas, C. (International Journal of Sports Science & Coaching, 2024)
The aim of this study was to quantify longitudinal changes in the games of the 6 Men`s European Handball Championship (EHC) celebrated between 2012 and 2022. A total of 563 match observations were examined. Specifically, the study contained the Number of Goals, Number of Attacks, Number of Shots, Number of Saves, Offensive Efficacy (Number of Goals/Number of Attacks × 100) and Defensive Efficacy (100 - Offensive Efficacy of the Opponent). Data were examined using the Kruskal-Wallis test and linear regression analysis. Results suggest that the number of goals remained relatively constant from 2012 to 2022. However, the number of attacks, shots, saves and defensive efficacy decreased, while offensive efficacy increased. These findings can contribute to a better understanding of how handball is evolving from a structural or tactical viewpoint.